Atmospheric transport of hydrogen sulfide from proposed geothermal power plant (unit 19): predictions by physical modeling in a wind tunnel - Cermak, Jack E., author; Petersen, Ronald L., author; Fluid Dynamics and Diffusion Laboratory, Fluid Mechanics and Wind Engineering Program, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1978)
Tests were conducted in the Colorado State University wind tunnel facility of the transport and dispersion of H2S plumes emanating from cooling towers positioned at three locations in the Geysers Geothermal Area. The wind tunnel tests were conducted with the cooling towers and terrain modeled to a scale of 1:1920. The first phase of the testing was conducted in the Environmental Wind Tunnel under neutral stratification. Ground level concentrations were measured in the vicinity of Anderson Springs and Whispering Pines for two wind directions and four wind speeds. The second phase of the testing was conducted outside the wind tunnel in a specially enclosed area. Nighttime drainage flow conditions were simulated by cooling the terrain. Concentration measurements in the vicinity of Anderson Springs were obtained as well as the velocity and temperature distributions of the resulting flow. A complete description of the test methodology, concentration measurements and flow visualization is included in the report.
CER78-79RLP-JEC10.
Prepared for Pacific Gas and Electric Company.
September 1978.
Keywords: Geothermal power plants -- Environmental aspects -- California -- Lake County; Wind tunnel models; Hydrogen sulfide